PENGGUNAAN METODE ABJAD JARI DAN BAHASA TUBUH SERTA MEDIA PEMBELAJARAN DALAM PEMBELAJARAN PAI BAGI ANAK BERKEBUTUHAN KHUSUS TUNARUNGU DI SLB NEGERI MUSI RAWAS - Yuliansyah Yuliansyah (Al-Bahtsu: Jurnal Penelitian Pendidikan Islam, 2018)
This research  aims to describe  the use of methods of the alphabet thumb  and  body  language in learning  islamic religious education on child tunarugu, and a utilization media learning in learning islamic religious education on child tunarugu and  to know factors factor inhibitors and  the utilization of media  supporters learning in learning islamic religious education on child tunarugu. The research  is descriptive  research  qualitative  and  is field research  (field research). But technique data  col- lection uses the observation, interview,  and  documentation. To analyse  data  using reduction data,  presentation of data  and the withdrawal  of conclusion,  checking  the validity of data  using triangulation. The result showed  1) use the alphabet fingers and  body  language in learning  islamic education had  gone  well, because this method suitable for children  with special needs disabled  athletes  tunarugu and  students  got the this method, 2) the use of media  learning used in learning religious education in using media  focus, media  pictures outboard (posters), reading  books and exercise pictures letters hijaiyah.  And media  letters hijaiyah  card,  3) supporting factors media  uses learning  that education teachers  who are willing to make  media  learning,  the interest  and  the motivation to study students  because medium  used  will attract  learning,  and  the other  facilities support. But factors that does not support  is limited of education facilities and  infrastructure, the absence of special teachers  islamic educa- tion, students  who have  limited so it takes the old process  in learning,  lack of the guidance and  motivation learn from parents or guardian students  to his son.